2019
DOI: 10.1007/s00125-018-4788-7
|View full text |Cite
|
Sign up to set email alerts
|

Association and risk factors of chronic kidney disease and incident diabetes: a nationwide population-based cohort study

Abstract: Aims/hypothesis Chronic kidney disease (CKD) is a known complication of diabetes mellitus, and insulin resistance is a well-known complication of CKD. However, there is no consensus in the published data on the association of CKD with incident diabetes. Methods A total of 15,403 people with CKD were identified from the Taiwan National Health Insurance Research Database to determine their risk of incident diabetes compared with that of 15,403 matched individuals without CKD. Fine and Gray regression models usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Moreover, there is a reverse causality that CKD is a risk factor of incident diabetes. 46 Recently, one study conducted MR analysis to determine the causal relationship between type 2 diabetes and decreased renal function in 11 502 Chinese population. 47 They reported that GRS associated with type 2 diabetes, insulin resistance, and insulin sensitivity had a significant relationship with decreased eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a reverse causality that CKD is a risk factor of incident diabetes. 46 Recently, one study conducted MR analysis to determine the causal relationship between type 2 diabetes and decreased renal function in 11 502 Chinese population. 47 They reported that GRS associated with type 2 diabetes, insulin resistance, and insulin sensitivity had a significant relationship with decreased eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this discrepancy might be explained by the differences in the method of survival analysis. A competing risk might have been prevalent in the CKD population 16 , 17 . In this regard, progression to ERSD and pre‐ESRD death compete with each other, because pre‐ESRD death completely hinders any observation of the progression to ESRD, as does the ESRD progression to pre‐ESRD death 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, progression to ERSD and pre‐ESRD death compete with each other, because pre‐ESRD death completely hinders any observation of the progression to ESRD, as does the ESRD progression to pre‐ESRD death 17 . Conventional survival analyses, including the Kaplan–Meier method and Cox proportional hazards model that were used previously, treated competing events as non‐informational censored data, presumably causing an overestimation of the cumulative incidence of the primary event of interest 16 , 17 . To overcome these issues, we used a competing risk model to evaluate the effect of depression severity on progression to ESRD and pre‐ESRD death.…”
Section: Discussionmentioning
confidence: 99%
“…Another population-based cohort study in Taiwan found that CKD was a significant and independent predictor of incident diabetes(adjusted HR 1.204; 95% CI 1.11, 1.31) [19].…”
Section: Discussionmentioning
confidence: 99%